Forest fires and economic incentives: impact of forest protection laws in Argentina - Lema, Rolando Daniel; Egolf, Patricia (International Association of Agricultural Economists (IAAE), 2020)
This paper evaluates the potential impact of the recently enacted forest protection laws on the number of forest fires in Argentina. The forest protection laws (at a federal and provincial level) restricts the use of forestry land in several ways, and limit the expansion of the agricultural frontier. This restriction can make forest arson potentially profitable to clear land and to expand the agricultural frontier circumventing the laws. We present a conceptual model based in the economic theory of crime to analyze forest arson decisions, and to predict individual behavior. Using panel data from 2002 to 2014 at a provincial level we present empirical evidence of systematic effects in the occurrence of forest fire as a function of the new regulation and its sequential implementation. Fixed effects and difference-in-differences estimates show that the number of fires increased transitory some 100% -200% in the main crop producer provinces during the law implementation process (2009-2011).